A Decade of KDIGO updates (2012–2025): What’s new in the evaluation and management of anemia in chronic kidney disease? - Indriyani, Fonna; Wahyudi, Hendra (Svāsthya: Trends in General Medicine and Public Health, 2025)
Anemia is a prevalent complication of chronic kidney disease (CKD) that leads to adverse clinical outcomes, increased rates of morbidity and mortality, and increased healthcare costs. The recently updated KDIGO 2025 Anemia in CKD Guideline substantially updates the 2012 version, incorporating the latest clinical evidence and expert consensus to improve patient care in CKD patients. This review examines the updates in the KDIGO 2025 Anemia in CKD Guideline compared with the 2012 version, highlighting advancements in diagnosis, evaluation, and management to improve patient outcomes. A comprehensive analysis of the published literature, guideline updates, and clinical studies was conducted to assess changes in the diagnostic and evaluation criteria, treatment approaches, and therapeutic recommendations for anemia in CKD patients. The diagnosis and evaluation of anemia in CKD emphasize a more individualized, risk-based approach that considers the patient’s stage of CKD. Optimizing iron status and addressing inflammation before initiating ESA therapy should be prioritized to minimize the risk of complications. HIF-PHIs are alternative therapies for patients with ESA resistance or an increased risk of ESA-related complications. A structured framework for managing ESA hyporesponsiveness can classify high-risk patients and promote alternative interventions, such as iron optimization and HIF-PHIs, instead of ESA dose escalation. The updated guidelines largely maintain unchanged transfusion practices. The KDIGO 2025 guidelines represent a major evolution in the evaluation and management of anemia in CKD patients, building on the 2012 recommendations with more precise and individualized treatment strategies. These updates optimize treatment efficacy, reduce complications, and enhance patient outcomes.